2000
DOI: 10.1034/j.1399-0012.2000.140211.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic photopheresis and chronic rejection: effects on graft intimal hyperplasia in cardiac transplantation

Abstract: In this small pilot study, photopheresis is a safe, well-tolerated immunomodulatory technique that is capable of decreasing the severity of chronic rejection manifesting as post-transplant graft intimal hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 12 publications
1
62
0
3
Order By: Relevance
“…Subsequent clinical trials supported the prophylactic use of photopheresis in posttransplantation patients. 141,142 In a pilot study of 23 heart transplant recipients, Barr et al 142 used photopheresis prophylactically beginning …”
Section: Photopheresismentioning
confidence: 99%
“…Subsequent clinical trials supported the prophylactic use of photopheresis in posttransplantation patients. 141,142 In a pilot study of 23 heart transplant recipients, Barr et al 142 used photopheresis prophylactically beginning …”
Section: Photopheresismentioning
confidence: 99%
“…[4][5][6][7] Extracorporeal photopheresis (ECP) has been shown to be efficacious in the treatment of cutaneous T-cell lymphoma (CTCL), selected autoimmune disorders and solid organ allograft rejection. [8][9][10][11][12][13][14][15][16][17][18] While the mechanism of action of ECP in autoimmune disorders is still not fully defined, it is believed that in CTCL patients, the combination of ultraviolet light and 8-methoxypsoralen induces apoptosis in a small subset of circulating clonal tumor or autoreactive T-lymphocytes, resulting in the stimulation of a cytotoxic T-cell response against the clone. 19,20 A number of retrospective reports have demonstrated efficacy of ECP therapy in patients with skin and visceral manifestations of cGVHD, but little information is available regarding prognostic or biological variables predictive of response.…”
mentioning
confidence: 99%
“…Additional series in patients with severe or recurrent heart transplant rejection reported that the addition of photopheresis reduced or reversed rejection episodes [49][50][51]. Barr et al [52] studied the effect of prophylactic photopheresis prospectively and concluded that it is a safe and well-tolerated immunomodulatory technique, and in one study, it is associated with a significant reduction in the frequency and severity of acute heart rejection episodes, and in a second study, it is associated with amelioration of chronic rejection (as judged by a reduction in coronary artery intimal hyperplasia in the transplanted heart) [53]. One of the largest studies of heart transplantation, a retrospective analysis of 343 heart transplant cases from Alabama, reported that photopheresis initiated in a subset of patients with high rejection risk resulted in a reduced rate of hemodynamic compromise and death from rejection [54].…”
Section: Solid Organ Transplant Rejectionmentioning
confidence: 96%